Impact of Energy Drinks on Students’ Health and Academics at a Private Nursing College (Journal of Rashid Latif Medical College, 2025)
Background:Energy drinks are increasingly consumed by college students in Pakistan, primarily for enhanced alertness and academic stamina. However, their potential cardiovascular effects and influence on academic performance remain controversial.Aim:This study aimed to assess the short-term effects of energy drink consumption on academic performance and cardiovascular indicators, including blood pressure and pulse rate, among nursing students in Pakistan.Methods:A randomized controlled experimental design was used. From 193 nursing students in Karachi, 50 habitual energy drink consumers were randomly selected and assigned to either an experimental group (received a commercial energy drink) or a control group (received bottled water). Pre- and post-intervention measures included systolic/diastolic blood pressure, pulse rate, and academic performance via standardized tests.Results:The experimental group showed an increase in mean systolic blood pressure from 119 to 125 mmHg and diastolic pressure from 70 to 74 mmHg. No significant changes were observed in pulse rate or academic performance within the group. However, systolic and diastolic blood pressure differences between the experimental and control groups were statistically significant (p < 0.05). Academic performance showed no significant difference between groups.Conclusion:Energy drink consumption among Pakistani nursing students may elevate cardiovascular indicators such as blood pressure but does not significantly impact academic performance in the short term. These findings highlight the need for awareness campaigns about the potential health risks of energy drink use.